Financial and Economic Security in the Field of Financial Markets at the Stage of European Integration - Novak, Anatolii; Pravdyvets, Oleksander; Chornyi, Oleksandr; Sumbaieva, Liudmyla; Akimova, Liudmyla; Akimov, Oleksandr; Сумбаєва, Людмила Петрівна; Правдивець, Олександр Миколайович (AOS-Estratagia and Inovacao, 2022)
Purpose: the aim of this article is to study the features of the financial and economic security of the integrated financial market of the EU Theoretical Framework: the concept of financial security was considered as a complex multi-tiered system. The theories of healthy competitive investment environment, and theory of capital markets functioning were employed in the study. Design/Methodology/Approach: the instrumental and methodological apparatus of the work is based on the use of general methods of scientific knowledge: comparison, abstraction, analysis and synthesis. Dialectical metod was used, as well as formal-logical, problem-theoretical, systemic-structural, and the method of comparative legal analysis. Findings: the EU has achieved noticeable success in providing economic security of financial markets over the past decades. The EU experience in this area can be considered the most complete. The uniqueness of this experience is also proven by the fact that it is based on national achievements and the centuries-old financial culture of the EU member states, among which several states are rightfully recognized as global financial players and have the status of international financial centers. Research, Practical and Social Implications: For global expert and regulators community, turning to the EU experience is not only valuable, but also relevant, under the necessity to consider the best world practices when creating a common financial market. Originality/Value: the EU experience in the field of financial and economic security of financial markets is systematized not at the level of individual EU members, but at the level of EU as a community in whole. © 2022 The authors.
Keywords: financial market; financial mechanism; integration; regulation; security